What’s a chance event? Contrasting different senses of ‘chance’ with Aristotle’s idea of meaningful unusual accidents - Maar, Alexander (Revista Archai, 2022)
In this article, we present and explain ten different possible meanings of a chance event – some ontological, some epistemic – and provide examples whenever possible. We describe and illustrate more carefully the view of chance (tyche) expressed by Aristotle in his Physics, a demanding and complex notion, and critically contrast it with the other senses examined, attempting to determine any (in)compatibilism.